Study on the Electro-Fenton Chemomechanical Removal Behavior in Single-Crystal GaN Pin–Disk Friction Wear Experiments - Yangting Ou; Zhuoshan Shen; Juze Xie; Jisheng Pan (Micromachines)
Electro-Fenton chemical mechanical polishing primarily regulates the generation of hydroxyl radicals (·OH) via the Fenton reaction through an applied electric field, which subsequently influences the formation and removal of the oxide layer on the workpiece surface, thereby impacting the overall polishing quality and rate. This study employs Pin–Disk friction and wear experiments to investigate the material removal behavior of single-crystal GaN during electro-Fenton chemical mechanical polishing. Utilizing a range of analytical techniques, including coefficient of friction (COF) curves, surface morphology assessments, cross-sectional analysis, and power spectral density (PSD) measurements on the workpiece surface, we examine the influence of abrasives, polishing pads, polishing pressure, and other parameters on the electro-Fenton chemical–mechanical material removal process. Furthermore, this research provides preliminary insights into the synergistic removal mechanisms associated with the electro-Fenton chemical–mechanical action in single-crystal GaN. The experimental results indicate that optimal mechanical removal occurs when using a W0.5 diamond at a concentration of 1.5 wt% combined with a urethane pad (SH-Q13K-600) under a pressure of 0.2242 MPa.